Материалы комаровской и сосницкой культур в экспозиции Археологического музея Института археологии НАН Украины - Лысенко, С.Д. (Археологія і давня історія України, 2019)
В статье рассмотрены керамика и бронзовые
украшения комаровской и сосницкой культур тшинецкого культурного круга (ТКК) из экспозиции Археологического музея Института археологии НАН Украины, происходящие с памятников лесостепной
Восточной Волыни (Войцеховка), Киевского (Украинка, Заваловка, Здвижевка, Плитовище, Гостомель) и
Черниговского (Угловая Рудня) Полесья. Находки относятся к различным периодам становления и развития ТКК и датируются в пределах ІІ тыс. до н. э. The article republishes the ceramics and bronze decorations of Komarovo and Sosnitsa cultures of the
Trzciniec cultural circle (TCC) from the exposition of the Archaeological Museum of the Institute of Archeology of
the National Academy of Sciences of Ukraine. Detailed descriptions of the exhibits and their author’s graphic
reconstructions are given. These things, which became a textbook long time ago, previously were published
only in the form of schematic and inaccurate drawings or in the form of not very high-quality photographs. The
materials originate from the sites of the northern part of the forest-steppe eastern Volhynia (Wojciechowka),
Kiev (Ukrainka, Zavalovka, Zdvizhevka, Plitovische, Gostomel) and Chernigov (Rudnya) Polesie. The finds
refer to different periods of the formation and development of the TСC and date back to 2nd thousand BC.